Advanced Drug Delivery Systems: Innovations and Applications in Modern Pharmacy - Ranganathan, Venkatalakshmi; Fazeela Mahaboob Begum S.M; Venkatesan, Santhosh; Rahamathullah, Mohamed Suhail; Barakkathulla, Akeela Farsana; Chinnappan, Sasikala (Pharmaceutical Research: Recent Advances and Trends Vol. 6, 2024)
Recent advancements in drug delivery systems have revolutionized the field of pharmacy, providing new avenues for targeted and controlled drug release. This chapter explores cutting-edge technologies in drug delivery, emphasizing passive and active targeting mechanisms, as well as stimuli-responsive systems. The chapter explores the design, benefits, and challenges of these advanced drug delivery systems. It discusses how these technologies improve therapeutic efficacy, minimize side effects, and enhance patient compliance. Furthermore, it addresses the current limitations and future directions of research in this field, emphasizing the need for interdisciplinary collaboration to overcome obstacles and develop innovative solutions. By providing a comprehensive overview of these advanced systems, this chapter serves as a valuable resource for researchers and practitioners aiming to optimize drug delivery strategies for better clinical outcomes.